L’Impact des corridors de la Région du Grand Mékong - Thomas Foin (EchoGéo)
Since the 1990s, the Greater Mekong Subregion (GMA), supported by the Asian Development Bank (ADB), has developed the corridors approach with the aim to promote regional integration in Southeast Asia. Economic corridors, which connect production and trade centers, induce at the scale of cities, new relations of complementarity and / or competition and a redefinition of their urban functions. Due to its location on the North-South Economic Corridor, Chiang Rai city, situated in northern Thailand, has undergone a process of urban reconfiguration and a specialization of its political and economic functions. The study of these recent dynamics allows to define Chiang Rai city as an urban pair.